A New Look At The Organizational Implications of Automation - Lipstreu, Otis; Reed, Kenneth A. (Academy of Management Journal, 1965)
The article investigates the organizational changes brought about by the introduction of automation technology in a baking plant. Information related to the impact of automation on the amount of supervisory responsibility and the plant's ratio of supervisors to workers is presented. A discussion is presented about the impact of automation on the plant's labor force. The study found that while automation allows for more efficient production of goods, it increases the work level of supervisors and managers.